Carbon doped with binary heteroatoms (N, X–C, where X = P, B, or S) derived from polypyrrole for enhanced electromagnetic wave absorption at microwave frequencies. Issue 3 (1st February 2023) - Chen, Liang; Liu, Fubin; Sui, Jing; Waterhouse, Geoffrey I.N.; Zhang, Zhi-Ming; Yu, Liang-min
Abstract: Dual heteroatom-doped carbon materials show great promise as electromagnetic wave absorbers. However, synthesizing carbons containing multiple heteroatoms at controlled heteroatom doping levels has provided challenges to date. Herein, we report a simple method for manufacturing dual heteroatom doped carbons (N, X–C, where X = P, B, or S) by direct carbonization of polypyrrole synthesized in the presence of H3 PO4, H3 BO3, or H2 SO4, respectively. The heteroatom content of the N, X–C products could be precisely tuned by varying amounts of acid dopant used in the polypyrrole synthesis. The N, X–C materials showed excellent electromagnetic wave absorption properties, especially N, S1 –C (prepared using equimolar amounts of pyrrole and H2 SO4 ) which offered a wide absorption bandwidth up to 6.6 GHz (11.38–18 GHz), and a RLmin of −32.3 dB (14.2 GHz) at 2.5 mm at a ﬁller loading of 9.0 wt%. The outstanding electromagnetic wave absorption performance of N, S1 –C was attributed to the presence of N dopant species, defects, C–S, and C–SOx groups, which optimized dipole polarization and conduction loss in the dielectric loss leading to excellent impedance matching.